Synthesis, Neuro-protection and Anti-cancer Activities of Simple Isatin Mannich and Schiff Bases - Chen, Gang; Ning, Yang; Zhao, Wei; Zhang, Yanqiu; Zhang, Yu; Hao, Xiaojiang; Wang, Ye; Mu, Shuzhen (Letters in Drug Design & Discovery, 2016)
The study of isatin, as well as its kind of derivatives, has become a hot topic for a long time. To explore the new compounds and bioactivities, in this work, a series of simple isatin Mannich and Schiff bases was synthesized through the condensation reaction. The structures of these synthesized compounds were characterized using NMR and MS. Furthermore, structure of one of these compounds (IMS-4) was studied by using single crystal X-ray diffraction. Then the anti-tumor and neuro-protection activities of these compounds were evaluated. The results showed that several compounds show protection activity on the PC12 cells apoptosis induced by H2O2, which are more effective than that of (±) α-Tocophreol (VE). Besides, some compounds also show anti-tumor activity against A549 and P388 cell lines more potent than that of isatin.
Keywords: Isatin